Genome-wide survey of the bipartite structure and pathogenesis-related genes of Neostagonosporella sichuanensis, a causal agent of Fishscale bamboo rhombic-spot disease - Liu, Lijuan; Yang, Chunlin; Liang, Fang; Li, Chengsong; Zeng, Qian; Han, Shan; Li, Shujiang; Liu, Yinggao (Frontiers in Microbiology, 2024)
Bamboo resources have garnered significant global attention due to their excellent capacity for regeneration and high yield. Rhombic-spot disease, a substantial threat to fishscale bamboo (Phyllostachys heteroclada), is primarily caused by Neostagonosporella sichuanensis. This study first reported the genome assemblies and characteristics of two N. sichuanensis isolates using PacBio and Illumina sequencing platforms. The genomes of N. sichuanensis strain SICAUCC 16-0001 and strain SICAUCC 23-0140, with sizes of 48.0 Mb and 48.4 Mb, respectively, revealed 10,289 and 10,313 protein-coding genes. Additionally, they contained 34.99% and 34.46% repetitive sequences within AT-rich regions, with notable repeat-induced point mutation activity. Comparative genome analysis identified 1,049 contracted and 45 expanded gene families in the genome of N. sichuanensis, including several related to pathogenicity. Several gene families involved in mycotoxin metabolism, secondary metabolism, sterol biosynthesis and transport, and cell wall degradation were contracted. Compared to most analyzed necrotrophic, hemibiotrophic, and phaeosphaeriacous pathogens, the genomes of two N. sichuanensis isolates exhibited fewer secondary metabolite enzymes, carbohydrate-active enzymes, plant cell wall degrading enzymes, secreted proteins, and effectors. Comparative genomics analysis suggested that N. sichuanensis shares more similar characteristics with hemibiotrophic pathogens. Based on single carbon source tests, N. sichuanensis strains demonstrated a higher potential for xylan decomposition than pectin and cellulose. The proportion of cell wall-degrading enzyme effectors occupied a high proportion of the total effectors of the N. sichuanensis genomes. These findings provide valuable insights into uncovering the pathogenesis of N. sichuanensis toward the efficient management of rhombic-spot disease of fishscale bamboo.